Generation of Flat Terahertz Noise by Mixing Incoherent Light Fields - Youwen Zhang; Wenjie Liu; Ya Guo; Junbin Liu; Zhiwei Jia; Yuehui Sun; Anbang Wang; Yuncai Wang (Photonics, 2023)
Terahertz (THz) noise sources play an irreplaceable role in testing THz devices and evaluating THz application systems, and the flatness of their radio frequency (RF) spectra is an important technical parameter. In this paper, a scheme for generating flat THz noise by mixing multiple filtered incoherent light fields is proposed. A theoretical analysis is conducted to investigate the impact of different spectral linewidths and central wavelength differences of incoherent light fields on the noise power and RF spectrum flatness, and an optimized experimental scheme is obtained. The results show that the proposed method can generate a 280–380 GHz flat THz noise signal with an RF spectrum flatness of ±0.5 dB in simulation and ±2.7 dB in our experiments. This article provides an excellent technical solution to the demand for flat THz noise in the THz field.